Influence of the thermohaline circulation on projected sea level rise - Knutti, Reto; Stocker, Thomas F. (American Meteorological Society, 2000)
A zonally averaged three-basin ocean–atmosphere model is used to investigate mean steric sea level rise in global warming scenarios. It is shown that if the North Atlantic deep water formation stops due to global warming, steric sea level rise is much larger for the same global mean atmospheric temperature increase than if the thermohaline circulation remains near the present state. In the equilibrium, global mean steric sea level rise depends linearly on the global mean atmospheric temperature increase. The influence of different subgrid-scale ocean mixing parameterizations on steric sea level rise is investigated.